Brian May's Red Special the story of the home-made guitar that rocked Queen and the world - May, Brian 1947-; Bradley, Simon (Hal Leonard, 2014)
Brian May and his father Harold started to hand-build an electric guitar in 1963. Brian dreamed of a guitar that would outperform any of the existing commercially made electric guitars; his father had the technical knowledge and skills to help make the dream come true. The written account is accompanied by original diagrams, sketches and notes dating from the building of the guitar, close-ups and x-rays, and photographs of Brian in performance